Strengthening the gluteus medius using various bodyweight and resistance exercises - Stastny, P.; Tufano, J. J.; Golas, A.; Petr, M. (Strength and Conditioning Journal, 2016)
The gluteus medius (gmed) is an important muscle and, if weak, can cause knee, hip, or lower-back pathologies. This article reviews methods of gmed strength assessment, provides exercises that target the gmed based on electromyography, presents how to implement gmed strengthening in heavy resistance training programs, and explains the importance of including these exercises in these programs.